2020
DOI: 10.1115/1.4047317
|View full text |Cite
|
Sign up to set email alerts
|

Sandstone Acidizing Using a Low-Reaction Acid System

Abstract: Sandstone acidizing is the process of removing the damage from sandstone reservoirs to restore the well productivity/injectivity to its original or expected rates. It differs from carbonate acidizing in which a substantial portion of the rock is dissolved. Stimulating sandstone with mud acid HF/HCl may cause many problems as sandstone is a clastic sedimentary rock that consists mainly of quartz, silica minerals, feldspars, clays, and minor quantities of zeolite and chlorites. When conventional mud acid reacts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…From constant K ads , the adsorption free energy ΔG ads can be determined as follows 45 = G RT K ln(55. 5 ) ads ads (17) where R is the universal gas constant, T is the thermodynamic temperature, and 55.5 is the molar concentration of water. 45 The calculated ΔG ads values of DTZA and DPZA in a 363 K environment are −34.62 and −28.90 kJ•mol −1 , respectively.…”
Section: Adsorption Isotherm and Thermodynamicmentioning
confidence: 99%
See 1 more Smart Citation
“…From constant K ads , the adsorption free energy ΔG ads can be determined as follows 45 = G RT K ln(55. 5 ) ads ads (17) where R is the universal gas constant, T is the thermodynamic temperature, and 55.5 is the molar concentration of water. 45 The calculated ΔG ads values of DTZA and DPZA in a 363 K environment are −34.62 and −28.90 kJ•mol −1 , respectively.…”
Section: Adsorption Isotherm and Thermodynamicmentioning
confidence: 99%
“…In practice, a mud acid-treated oil well normally undergoes rapid decline after an initial increase in oil production. Therefore, recently, chelating acid systems, which can realize high efficiency and rapid, uniform, and prolonged validity period of acidification, have been developed and have attracted significant attention. , Recent field applications proved that compared with conventional mud acid acidification, organic chelating acid can simplify the acidification process, reduce the total cost by decreasing the injected acid volume, and achieve a significantly increased production . Organic phosphonic acid, gluconic acid, lactic acid, etc., could be used as chelating acids.…”
Section: Introductionmentioning
confidence: 99%
“…Gomaa et al optimized the utilization of chelating agents in sandstone acidizing. DTPA and HEDTA were tested at different conditions using Berea sandstone cores.…”
Section: Applications Of Chelating Agents In Stimulationmentioning
confidence: 99%
“…In 2003, Rodoplu et al developed a mathematical model of "two acids and three minerals" to reflect the change of permeability, and the experimental results verified the validity of the model and the good agreement with the experimental results. 21 In 2005, Xie et al 22 further applied the small-scale model developed by Li et al 23 to study the conditions for earthworm pore formation during sandstone acidification, and the results showed that sandstone reservoirs with strong inhomogeneity are favorable for earthworm pore formation at low injection rates. A similar study was done by Morgenthaler et al Similar studies on the effect of inhomogeneity showed that the effect of inhomogeneity on permeability in small-scale lithology is greater than the effect of petrographic mineralogy on permeability.…”
Section: Introductionmentioning
confidence: 99%